Application of Contrast-Enhanced Sonography on the Diagnosis of Acute and Chronic Rejection After Renal Transplantation. Issue 1 (March 2020) - Cai, Ruiming; Tao, Liu; Liang, Weixiang; Lin, Minzhuan; Guo, Xuekun; Huang, Xian-en
Abstract : Abstract: To test the reliability of CEUS on the diagnosis of acute (AR) or chronic rejection (CR) after renal transplantation, patients who received renal transplantation in our center from January 2011 and December 2015 were retrospectively included in the current study. All the included patients underwent contrast-enhanced ultrasonography tests. Two regions of interests were chosen to carry out time-intensity curves (TICs). The main indexes include time indexes, intensity indexes, and difference indexes. Separation of TIC1 and TIC2 was evaluated by the authors. Results revealed that time to peak 1 (TTP-1), TTP-2, absolute time to peak 1 (ATTP-1), and ATTP-2 in the CR group were significantly later than those in the graft function stable group. Peak intensity 2 is smaller in the AR group than that in the GFS group, velocity of intensity ascending 2 is slower in the CR group than that in the GFS group, terminal intensity 1 (TI-1) and TI-2 are lower in the CR group than those in the GFS group, and Vd-1 is faster in the CR group than that in the GFS group ( P < 0.05). Those results indicated that contrast-enhanced ultrasonography test can satisfactorily reflect the microcirculation of transplanted kidney and can be used to assist in the early diagnosis of graft rejection.